1999
DOI: 10.1677/jme.0.0230013
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of both short and long forms of prolactin receptor mRNA in hypothalamic nuclei of lactating rats

Abstract: This study investigated expression of prolactin receptor (PRL-R) mRNA in selected hypothalamic nuclei of lactating rats (days 7-10 post partum) compared with dioestrous rats. Rat brains were frozen with liquid nitrogen and cut into coronal sections of 300 µm. From these sections, tissues were micropunched from the parietal cortex (CTX), choroid plexus (ChP), and five hypothalamic regions: supraoptic (SO), paraventricular (Pa), arcuate (Arc) and ventromedial hypothalamic (VMH) nuclei, and median eminence (ME). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 45 publications
(50 reference statements)
4
45
0
Order By: Relevance
“…In addition to changes in the long form of the PRL-R, in our previous studies we reported significant increases in short-form PRL-R mRNA expression in the paraventricular and ventromedial hypothalamic nuclei of lactating rats compared with dioestrous rats (Pi & Grattan 1999b). This was based on finding detectable levels of mRNA in lactating rats compared with almost undetectable levels during dioestrus.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In addition to changes in the long form of the PRL-R, in our previous studies we reported significant increases in short-form PRL-R mRNA expression in the paraventricular and ventromedial hypothalamic nuclei of lactating rats compared with dioestrous rats (Pi & Grattan 1999b). This was based on finding detectable levels of mRNA in lactating rats compared with almost undetectable levels during dioestrus.…”
Section: Discussionmentioning
confidence: 67%
“…The discrepancy between our previous studies and the present results may be explained by the different experimental procedures employed. The previous studies used conventional RT-PCR, which measured PCR product at the end of a set number of cycles of amplification, with high numbers of cycles required to produce a detectable signal (Pi & Grattan 1998b, 1999b. End-point measurements can vary in the amount of cDNA detected between duplicates of the same sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been reported that PRL enhances its own uptake in the choroid plexus (Mangurian et al 1992). Supporting this function, a high level of PRLR expression in the choroid plexus has been observed during lactation when the plasma PRL level is also high (Muccioli & Di Carlo 1994, Escalada et al 1996, Sugiyama et al 1996, Pi & Grattan 1999, Augustine et al 2003, Pi et al 2003, Nogami et al 2007, Anderson et al 2008. Also, PRLR expression in this brain region increases during the stress response, accompanying an increase in the plasma PRL level (Fujikawa et al 1995).…”
Section: Introductionmentioning
confidence: 82%